A Model of Developing Ability of Schizophrenia Patients Living in Community, Roi-Et Hospital - Sontoung, Aurapan; Phosung, Chusri; Khakhunmalee, Daungchun (Journal of Health Science of Thailand, 2018)
The frequent problems of caring for schizophrenia patients living in community were their loosing ability to relate with others while feeling unworthy and unable to earn a living while showing regression in some. Their relatives must stimulate them to carry on daily activities. The researchers wanted to develop ability of schizophrenia patients living in community, by action research in Amphoe Mueang Roi-Et in 2007- 2008, including 70 participants. Phase 1 was aimed at studying the situation of living in the community of schizophrenia patients by employing a quality research, covering 21 participants. Based on such finding, in phase 2, 33 participants collectively recommended a model of developing ability of schizophrenia patients living in community, and in phase 3 the model was implemented. Most data collection was carried out in in-depth interview, focus group discussions and evaluation on ability of schizophrenia patients living in community questionaires with alpha Cronbach’s alpha coefficient of 0.75. Descriptive statistics percent, mean and standard deviation, and content analysis were employed in data analyses. It was found that integration of schizophrenia patients into the community needed understanding and strong suppport from caregivers, community leaders and family members. In that connection, the pafients participated in family camp with programs on development of rehabilitation skill on living in community and occupational skill rehabilitation programs. As such, scores on their ability to live in community were higher than before.